Graphitic carbon nitride (g–C3N4)–based semiconductor as a beneficial candidate in photocatalysis diversity. (26th January 2022) - Hayat, Asif; Al-Sehemi, Abdullah G.; El-Nasser, Karam S.; Taha, T.A.; Al-Ghamdi, Ahmed A.; Jawad Ali Shah Syed,; Amin, Mohammed A.; Ali, Tariq; Bashir, Tariq; Palamanit, Arkom; Khan, Javid; Nawawi, W.I.
Abstract: Due to the future uses of solar energy in different areas, such as the oxidation of fossil fuel-based contaminants, the reduction of carbon dioxide, heterogeneous photocatalysis, and the generation of inexhaustible and renewable hydrogen gas exploits semiconductors. As a metal free photocatalyst, graphitic carbon nitride (g-C3 N4 ) is classified to solve these energy hazards and ecological difficulties owing to its excellent electronic structure with band energy of about 2.7 eV, robust photochemical stability, and better light-harvesting efficiency. However, its photocatalytic performance is still insufficient due to a minor surface area and poor conductivity. Therefore, heterojunction formation by combining it with a giant band gap material is a potential approach to reestablish polarization in its distinctive band structure, increase its light absorption capacity and enhance its surface area. In this regard, various synthesis techniques have been applied so far to integrate g-C3 N4 and other materials for boosting its photocatalytic activity. So far, metal oxide, sulfides, and ferrites are three crucial groups of materials that have been identified and defined to be used to synthesize g-C3 N4 dependent nanocomposites. As a result, in this review, we have compiled a list of the most recent g-C3 N4 nanocomposites with their applications in solar energy adaptation and pollution control. This study concludes an overview about the next steps to study the nanomaterials based g-C3 N4 composites and a range of additional insights to solve the present problems. Highlights: This review addresses the properties and structures of g-C3 N4 photocatalyst structure. Pros and cons of their synthesis techniques. The types of the g-C3 N4 -based nanocomposite are emphasized. Approaches to improve the photocatalytic activity of g-C3 N4 . The most up-to-date photocatalytic applications were thoroughly discussed.